Financial socialization and moderation effect of gender in the influence of financial behavior on financial well-being among young adults - Anthony, Mervin; Sabri, Mohamad Fazli; Abdul Rahim, Husniyah; Othman, Mohd. Amim (Malaysian Consumer and Family Economics Association MACFEA, 2022)
Personal financial success is desired by young adults through their upbringing since childhood and may differ among men and women. In conjunction with these, the objective of this study was to assess the influence of financial socialisation on financial behaviour and financial well-being. It further analysed how the gender of young adults moderates the influence of financial behaviour on financial well-being. The conceptual framework was examined by subjecting data of 360 young adults to structural equation modelling (SEM). Multistage random sampling was used to sample the respondents. The results displayed a significant influence of financial socialisation on financial behaviour and the financial well-being of young adults. The results indicated the insignificant moderating effect of males in the influence of financial behaviour on financial well-being (β = 0.26, t = 1.388, p = 0.16). Meanwhile, the results indicated a significant moderating effect of females in the influence of financial behaviour on financial well-being (β= 0.73, t = 2.649, p = 0.08). This paper finds that the influence of financial behaviour on financial well-being depends on the gender of respondents, whereby the effect is not significant for male respondents, while the effect is significant for female respondents. In conclusion, the study concludes that the moderation by gender occurred, which impacts their financial well-being.